The Comprehensive Income Statement in the Light of FASB and IASB Regulations - Bek-Gaik, Bogusława (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The basic objective of financial statements, which provide useful information to a wide audience (the role of the information report), has for years been the subject of discussion among organisations responsible for the accounting regulations in the world. The activities of entities were a matter of particular importance to the Accounting Standards Board that implemented the concept of comprehensive income from 1 January 2009. The article focuses on the requirements and form of presentation of the statement of comprehensive income according to FAS 130 and IAS 1.